-Reading the poems in beginnings of Islam era Hassan bin Thabit poem in the Lament of the battle the martyrs of Mu'tah - Stylistic study - Al-Mualid, Rawda (Journal of Humanities & Social Sciences, 2018)
This study aimed at making use of the modern inclinations in the linguistic study represented in the stylistic way، which gives a chance to accurately follow the poetic text with all its different and variant levels to uncover the aesthetic values and the stylistic domination that reflects the poet's perception of death and life where he starts off from the language and finishes up to it.This study also deals with a poem by Hassan Bin Thabit in a lament for the martyrs in the battle of Mu'tah in a stylistic way. Even though there have been many studies that dealt with the poetry of Hassan Bin Thabit from an artistic and historical scope، this study has taken the stylistic methodology as an entry to access reading the poem and analyzing it and classifying the stylistic levels which are represented in the vocal level that is related to the Islamic poet's state، and the picturing level that is represented in the visual and coloring picture and the constructional and referential level that is represented in in the poetic dictionary of this lament.The study results concluded that the most important of which are؛ the constructional level of the lament poem was so important through the verbal and noun clauses variation where the verbal clauses dominated the noun clauses plus many other styles. there was a clear desire in Hassan Bin Thabit to do away with the grieving poetic condition by using these styles.
Keywords: Poetic heritage; rhythmic structure; stylistic phenomena